Perfil bacteriológico de biópsia pulmonar e lavado traqueobrônquico de equinos sadios mantidos em sistema extensivo e estabulado - Duarte, Rodrigo Rolim [UNESP] (2007)
The differences in stabling conditions may influence the microbiota in airway of healthy horses, and consequently result changes in airway infections. Diagnosis of airway affections may be reach by using tracheobronchial (TB) wash and pulmonary biopsy as well. The aim of this study was to evaluate the pulmonary and TB microbiota in healthy horses submitted to different stabling. Eighteen healthy adult male quarterhorses were distributed in two groups: Group 1 (nine animals maintained in extensive regimen); and Group 2 (nine animals kept in stall conditions). The washes were carried out using physiologic solution in TB lumen through the intravenous catheter (14G x 30 cm). Pulmonary biopsies were collected using semiautomatic Tru-cut needles (16G x 20 cm). The material collected was submitted to microbiological culture. No trickiness was observed in the animals. At least one species of bacteria grown in wash tracheobronchial culture in the horses studied. In TB washes was observed predominance both of Gram negative and facultative aerobic microorganisms. In 38.5% out of the washes were isolated Gram-positive coccus, predominantly Staphylococcus. Escherichia coli and Enterobacter were isolated in 3% and 11%, respectively. The culture of airway in stabling animals showed a higher number of isolates in both wash and biopsy techniques comparing to the horses kept in extensive regimen.